Freeform fabrication of fiber-reinforced hydrogels using direct-write far-field electrospinning. (October 2020) - Nowak, James F.; Clippinger, Aaron; Samuel, Johnson
Abstract: Fiber-reinforced hydrogels are a class of soft composites that are seeing increased use in tissue engineering, regenerative medicine, and bio-printing. These hydrogels exhibit mechanical and biological properties that are similar to those found in living tissues. While advancements are being made on the biological feasibility of fiber-reinforced hydrogels, there are limits to the geometries realized using electrospinning techniques. To this end, the objective of this paper is to develop a freeform fabrication process that addresses two key limitations of existing fiber-reinforced hydrogel manufacturing processes, viz., their inability to manufacture (i) tall structures in the tens of millimeters height range; and (ii) structures with external overhangs. The freeform fabrication process involves the use of a direct-write far-field electrospinning print-head that enables the printing of specific electrospun fiber layers based on the cross-sectional geometry of the part. These fiber layers are then stacked to create a three-dimensional fiber pre-form. Finally, the fiber pre-form is submerged in specific hydrogel and cross-linking solutions to realize the fiber-reinforced hydrogel part of interest. In order to create an external overhang, a sacrificial support material is incorporated using hydrophobic fiber pre-forms to resist the infiltration of the hydrogel solution during the submersion step. The process has been successfully demonstrated both for thin parts with contours, and vasculature-mimicking tubular structures. Mechanical testing of the ∼1.6 wt. % fiber-reinforced hydrogels shows an order of magnitude improvement in the tensile properties when compared to published results for pure hydrogel.